1999
DOI: 10.1103/physrevb.59.3195
|View full text |Cite
|
Sign up to set email alerts
|

In situXPS analysis of various iron oxide films grown byNO2-assisted molecular-beam epitaxy

Abstract: We report on a systematic analysis of x-ray photoelectron spectroscopy ͑XPS͒ core-and valence-level spectra of clean and well-characterized iron oxide films, i.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

94
497
2
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,061 publications
(596 citation statements)
references
References 32 publications
94
497
2
3
Order By: Relevance
“…Figure 1 shows the Fe 2p core-level XPS spectrum of the ZnO:Fe nanoparticles in comparison with those of ␣-Fe 2 O 3 ͑Fe 3+ ͒, 23 FeO ͑Fe 2+ ͒, 23 and Fe 3 O 4 ͑Fe 3+ -Fe 2+ mixed-valence͒. 24 The Fe 2p 3/2 peak of the ZnO:Fe nanoparticles is split into two peaks at E B ϳ 710 and ϳ708 eV, corresponding to the energy positions of ␣-Fe 2 O 3 and FeO. The XPS spectrum of the ZnO:Fe nanoparticles therefore reflects an Fe 3+ -Fe 2+ mixed-valent state of the Fe ions in agreement with the previous Mössbauer report.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 shows the Fe 2p core-level XPS spectrum of the ZnO:Fe nanoparticles in comparison with those of ␣-Fe 2 O 3 ͑Fe 3+ ͒, 23 FeO ͑Fe 2+ ͒, 23 and Fe 3 O 4 ͑Fe 3+ -Fe 2+ mixed-valence͒. 24 The Fe 2p 3/2 peak of the ZnO:Fe nanoparticles is split into two peaks at E B ϳ 710 and ϳ708 eV, corresponding to the energy positions of ␣-Fe 2 O 3 and FeO. The XPS spectrum of the ZnO:Fe nanoparticles therefore reflects an Fe 3+ -Fe 2+ mixed-valent state of the Fe ions in agreement with the previous Mössbauer report.…”
Section: Methodsmentioning
confidence: 99%
“…Two weak but well defined peaks at approximately 710.8 eV and 724.2 eV, are observed, in agreement with the typical values of the Fe 2p 3/2 and 2p 1/2 core-level XPS peaks for ferric oxides. 21,22 In addition, the main Fe 2p 3/2 and 2p 1/2 peaks are accompanied by weak satellite structures on their high binding energy side, about 8 eV above the respective Fe 2p line. Such a spectrum is typical of Fe 2 O 3 oxides ͑␣-and ␥-Fe 2 O 3 polymorphs͒.…”
Section: A Tem Xrd and Xps Techniquesmentioning
confidence: 98%
“…The Fe 2p spectra revealed that iron exists predominately as Fe 3+ , with a 2p 3/2 peak position of 710.9 eV. [28] Of interest is the location of the 2p 3/2 shake-up satellite peak. For moderate heat treatments, a characteristic hematite satellite peak at approximately 719 eV was observed.…”
mentioning
confidence: 99%
“…[28] Introduction of tetravalent Sn ions into the hematite lattice by either substitution or by occupation of vacant interstitial sites requires partial reduction of Fe to maintain charge neutrality, and could account for the observed satellite behavior. [29,30] It has been proposed that the mutual existence of Fe in two valence states creates a hopping mechanism for conductivity that may contribute to improved PEC performance.…”
mentioning
confidence: 99%